PENGARUH DISIPLIN KERJA, KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ARTKEA INTERNUSA DIVISI LACE BY ARTKEA JAKARTA SELATAN - Sulistiani; Tarwijo (Journal of Research and Publication Innovation, 2024)
Sulistiani (201010503358), Management Study Program, Faculty of Economics and Business, Pamulang University, 2024. The Effect of Work Discipline, Safety and Health. Health and Safety on Employee Performance, South Jakarta. Supervised by Mr. Tarwijo, S.E., M.M. The purpose of this research is to know and analyze the Discipline Work Discipline, Safety and Health to Employee Performance at PT Artkea Internusa Lace By Artkea Division, South Jakarta. In this study the authors used descriptive quantitative methods. This research was conducted on employees at PT Artkea Intenusa Lace By Artkea Division, South Jakarta. With The data collection technique used is a questionnaire that has been tested for validity and reliability and data analysis techniques. The data collection technique used is a questionnaire that has been tested for validity and reliability and the data analysis technique used is multiple linear regression analysis and data analysis. The data analysis technique used is multiple linear regression analysis and hypothesis testing, namely the F test and T test. The results of this study are (1) work discipline, occupational safety and health together have a positive and significant on employee performance (2) work discipline does not have a significant influence on employee performance (3) work discipline, safety and health a significant influence on employee performance (3) safety and health There is a significant influence on employee performance.